KEPRIBADIAN TOKOH RIDHO DALAM NOVEL TUHAN MAAF ENGKAU KUMADU KARYA AGUK IRAWAN M N: KAJIAN PSIKOLOGI SASTRA - Julian MC Kitaro; Rusdian Noor Dermawan (CARAKA, 2015)
This research aims to describe: (1) Plot used the author to convey a psychological dimension. (2) the characters and characterizations author used to convey a psychological dimension. (3) setting that is used to convey the author's psychological dimension. (4) the personality of the characters in the novel Tuhan Maaf Engkau Kumadu by Aguk Irawan M.N. based on aspects of psychology. (5) the factors affecting psychological personages Ridho. The data of this research in the form of documentation in the form of a quote with the data source is a novel Tuhan Maaf Engkau Kumadu by Aguk Irawan M.N. Data collection is done with the technique of reading and note, while data analysis is done by qualitative descriptive analysis techniques with three steps, namely (1) reading the repetitively novel Tuhan Maaf Engkau Kumadu. (2) reading and studying literature, reference or references that have relationships and support towards issues and problems in this research. (3) records and entering data into the data analysis instruments. The data was then validated by the method of triangulation, i.e. the Act test or check the data findings with other findings while the absence of contrasts or the origin of the congruency between one another. Descriptive research results indicate that: (1) flows into three stages, namely the beginning, middle, the end. Ridho has internal and external conflict. (2) the main character Ridho most involved with the significance and themes, most related to other figures, most require time-telling. Explanatory character Eva Ratu Nisa, Afandi Irwan, Shaykh Radullah al Farghani, Nabila al Farghani, Mr. Ardiansyah, Sutirman, Sumaryati affecting the psychological dimension figure Ridho. Characterizations Ridho, i.e. believe in dreams, belief in omens, stubborn, strong-willed, timid, concerned, hard-working, smart, good-natured, polite, and polite. (3) social background affects the psychological dimensions of Ridho as a hard worker. (4) the personality of the Ridho is dominated by a repressed id resulting in the appearance of a conflict on the structure of personality. The conflict caused the psychotic hallucinations. In terms of psychology, Ridho suffered from schizophrenia. (5) there are two factors that influence psychological factors, i.e. endogenous Ridho, and exogenous factors. Endogenous factors in the form of a trust to excessive dreams and omens, as well as introjection of the elderly. Exogenous factors of experience of life and psychological pressure jilted from the family environment.